Optimal synthesis and new understanding of P2-type Na2/3Mn1/2Fe1/4Co1/4O2 as an advanced cathode material in sodium-ion batteries with improved cycle stability - Chu, S.; Wei, S.; Chen, Y.; Cai, R.; Liao, K.; Zhou, W.; Shao, Zongping (Elsevier Science Ltd, 2017)
© 2017. A sol-gel method with ethylene diamine tetraacetic acid and citric acid as co-chelates is employed for the synthesis of P2-type Na 2/3 Mn 1/2 Fe 1/4 Co 1/4 O 2 as cathode material for sodium-ion batteries. Among the various calcination temperatures, the Na 2/3 Mn 1/2 Fe 1/4 Co 1/4 O 2 with a pure P2-type phase calcined at 900°C demonstrates the best cycle capacity, with a first discharge capacity of 157mAhg -1 and a capacity retention of 91mAhg -1 after 100 cycles. For comparison, the classic P2-type Na 2/3 Mn 1/2 Fe 1/2 O 2 cathode prepared under the same conditions shows a comparable first discharge capacity of 150mAhg -1 but poorer cycling stability, with a capacity retention of only 42mAhg -1 after 100 cycles. Based on X-ray photoelectron spectroscopy, the introduction of cobalt together with sol-gel synthesis solves the severe capacity decay problem of P2-type Na 2/3 Mn 1/2 Fe 1/2 O 2 by reducing the content of Mn and slowing down the loss of Mn on the surface of the Na 2/3 Mn 1/2 Fe 1/4 Co 1/4 O 2 , as well as by improving the activity of Fe 3+ and the stability of Fe 4+ in the electrode. This research is the first to demonstrate the origin of the excellent cycle stability of Na 2/3 Mn 1/2 Fe 1/4 Co 1/4 O 2 , which may provide a new strategy for the development of electrode materials for use in sodium-ion batteries.